Inhibition of HT-29 colon cancer cell cultures by extracts from biodiverse germplasm sources of Solanum tuberosum L. - Zuber, Tatiana, author; Stushnoff, Cecil, advisor; Holm, David G., committee member; Byrne, Patrick F., committee member; Thompson, Henry J., committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: antioxidants; cell culture; growth inhibition; HT-29 colon cancer; immature potato; pigmented